ANDROID-BASED SHUTTLE ORDER APPLICATION USING FRAMEWORK FLUTTER - Mochammad Muslih Maruzi; Dadang Iskandar; Yogiek Indra Kurniawan (Jurnal Teknik Informatika (Jutif), 2022)
The shuttle ticket order process is the main process when someone is going to travel using shuttle transportation. The process of ordering shuttle tickets by visiting shuttle pool in the area or ordering by call has several problems that often make prospective passengers feel a lack of effectiveness and efficiency. This study aims to create an application that makes it easier for prospective passengers to order shuttle tickets and obtain shuttle information and make it easier for service providers to manage fleets and manage orders. This application created by using the waterfall method. The main stages in the system development life cycle in this method, namely: analysis, design, coding, and testing. This application is divided into two parts, Android-based using the Flutter Framework for potential passengers and web-based with PHP programming language for service providers. Black Box test results show valid results, which means the application is as expected. The results of the User Acceptance Test show an average value of 87% in "Very Good" category, which means this application is feasible to use.